(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores contemporary innovations in macro and microeconomics, focusing on technological, theoretical, and practical advancements. The paper examines significant contributions from recent literature, highlights innovative methodologies, and discusses the implications of these innovations for policy-making and business strategies.